Implementation of Teaching Materials Using Building Modeling and Information Design Based on the Green Building Concept at State Vocational School 3 Tondano - Saruendo Winowatan; Parabelem Tinno Dolf Rompas; Rolly Robert Oroh (International Journal of Information Technology and Education, 2026)
This study aims to develop a model of teaching materials for the Building Information Modeling (BIM) subject integrated with the green building concept, in order to improve students' understanding and awareness of the principles of sustainability in building design. The background of this study is based on the need for teaching materials relevant to the development of the modern construction industry, especially the application of Building Information Modeling (BIM) and global demands for sustainable development. The research method used is Research and Development (R&D) with the Borg & Gall development model consisting of ten stages, starting from preliminary studies to product trials. The research subjects consisted of vocational high school students majoring in BIM and learning media. The instruments used included interviews, validation questionnaires, observation sheets, and comprehension tests. The results of the study indicate that the developed teaching material model meets the eligibility criteria in terms of content, presentation, language, and visual appearance based on expert validation results. Limited trials indicate an increase in students' understanding of the BIM concept and green building principles with N-Gain scores in the medium to high category. In addition, student responses to the teaching materials are very positive, indicating that this model is interesting, easy to understand, and relevant to the needs of the workplace. Thus, this teaching material model is suitable for use in DPIB learning and is recommended for implementation as part of strengthening technology- and sustainability-based curricula in vocational education